2015
DOI: 10.1155/2015/912713
|View full text |Cite
|
Sign up to set email alerts
|

The Human IL-22 Receptor Is Regulated through the Action of the Novel E3 Ligase Subunit FBXW12, Which Functions as an Epithelial Growth Suppressor

Abstract: Interleukin- (IL-) 22 signaling is protective in animal models of pneumonia and bacteremia by Klebsiella pneumoniae and mediates tissue recovery from influenza and Staph aureus infection. We recently described processing of mouse lung epithelial IL-22 receptor (IL-22R) by ubiquitination on the intracellular C-terminal. To identify cellular factors that regulate human IL-22R, we screened receptor abundance while overexpressing constituents of the ubiquitin system and identify that IL-22R can be shuttled for deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…There is increasing interest in the role of E3 ligase proteins in pulmonary inflammatory conditions. We have previously shown a role for several E3 ligase proteins and subunits in acute lung injury and in pulmonary fibrosis (FIEL1) (24, 26, 27, 3740). The emerging paradigm is that modulation of specific E3 ligase activity may be a strategy to modify substrate protein levels in pathophysiologic states, such as acute lung injury, or in the progression of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing interest in the role of E3 ligase proteins in pulmonary inflammatory conditions. We have previously shown a role for several E3 ligase proteins and subunits in acute lung injury and in pulmonary fibrosis (FIEL1) (24, 26, 27, 3740). The emerging paradigm is that modulation of specific E3 ligase activity may be a strategy to modify substrate protein levels in pathophysiologic states, such as acute lung injury, or in the progression of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The SCF complex in particular targets phosphorylated substrates for ubiquitination through a recognition module, F-box protein. After overexpressing a library of F-box plasmids (24)(25)(26)(27) in B2B cells in a preliminary screen, we identified that one F-box component, FBXO10, was sufficient to decrease RAGE protein levels in B2B cells (Fig. 7A).…”
Section: E3 Ligase Subunit Fbxo10 Targets Rage For Ubiquitination Andmentioning
confidence: 99%
“…Further, IL-22 was shown to inactivate GSK3β, perhaps as a feedback mechanism to terminate IL-22Ra1 signaling. IL-22Ra1 was also shown to be regulated via ubiquitination by the E3 ligase FBXW12 (25). This interaction destabilizes IL-22Ra1.…”
Section: Influenza Infectionmentioning
confidence: 98%
“…On the other hand, FBXW12 is reported to be deleted or methylated in epithelial ovarian cancer (Chesnaye Ede et al, 2015). Interestingly, knockdown of FBXW12 increases human epithelial cell growth and cell cycle progression (Franz et al, 2015), suggesting that FBXW12 is an epithelial growth suppressor probably by inhibiting cell cycle progression.…”
Section: Roles Of Fbxw Sub-family In the Regulation Of Cell Cyclementioning
confidence: 99%